Peningkatan Pelayanan Calon Penumpang Kapal Studi Kasus di Perusahaan Pelayaran - Eni Tri Wahyuni; Aan Rubiyanto (Dinamika Bahari, 2021)
Shipping companies engaged in services are very concerned about service users. One of the companies engaged in services, especially on passenger ships, is very concerned about the satisfaction of service users for the sustainability of the company. This study aims to find out how the passenger service at PT Atosim Lampung Pelayaran is implemented at the Port of Tanjung Emas Semarang. It is hoped that with good service, passenger service time will be faster and more efficient. However, in the process of serving passengers at PT Atosim Lampung Shipping Semarang branch is still experiencing several obstacles that affect the service of prospective passengers. These obstacles are caused, among others: lack of understanding of ticket buyers in ordering tickets and checking schedules online, ineffective health services at PT Atosim Lampung Shipping Semarang branch. The research method used is a qualitative research method by conducting interviews, observations and literature studies. This study found that in order to improve services to prospective ship passengers, PT Atosim Lampung Pelayaran developed an online ticket booking system and improved health facility services.